Efficiency and safety of glycosaminoglycan-peptide complex in the therapy of chronic pain exacerbations in osteoarthritis of knee-joints in comorbid patients (results of DARTS observation program) - A. V. Naumov; O. N. Tkacheva; Yu. V. Kotovskaya; N. O. Hovasova (Лечащий Врач)
The article presents the results of complex observational program which includes drug and non-drug methods of treatment of recurrent chronic pain in osteoarthritis in comorbid patients. The most important components of this program are application of glycosaminoglycan-peptide complex and physical exercises. Special attention is paid to patients with comorbid diseases as the most widespread group of patients disposed to polypharmacy and having contraindications for NSAID administration.